The presentation and pregnancy outcome among teenage parturients in state specialist hospital, Asubiaro, Osogbo, Southwestern, Nigeria - Olalekan Olugbenga Awolola (Wolters Kluwer Medknow Publications, 2018)
Background: Teenage pregnancies are pregnancies between the age group of 13 and 19 years. Such pregnancies are categorized as high-risk pregnancies worldwide. This makes monitoring during the antenatal, intrapartum, and puerperal periods highly important. Objectives: The aim of this study is to determine the incidence, the mode of presentation, and the materno-fetal outcome in teenage parturients and compare with a control group. Materials and Methods: this prospective case-control study, recruited 63 teenage parturients who presented in labor ward in active phase labour between February 2013 and January 2015. These teenage parturients were matched with a control group in terms of parity and cervical dilatation of not less than or more than 1 cm (+1 cm), but are of age, 22-30 years. Thus, a total number of 126 parturients were studied. The mothers and their babies were followed up until the first 7th day postpartum. Results: In this study, 39 (61.90%) and 24 (38.10%) were married and unmarried, respectively, among the teenage parturients, whereas 60 (95.24%) and 3 (4.7%) were married and unmarried among the control group. Majority of the teenage parturients, 57 (90.47%) had only primary and secondary education, while 59 (93.47%) among the controls had secondary and tertiary levels of education. There were statistically significant differences in the incidences of genital lacerations (9 [14.28%] and 2 [3.18%]: P < 0.05), and the incidences of anemia in pregnancy (9 [14.28%] vs. 2 [3.18%]: P < 0.05) in the teenage and the older parturients. The other outcome measures in the two groups were similar. Conclusion: This study showed that teenage pregnancies with good antenatal, intrapartum, and neonatal care, gives almost the same materno-fetal outcomes as the control group. The determining factors for poor maternal and fetal outcomes are poor socioeconomic status and lack or poor quality of antenatal, intrapartum, and puerperal care.